Inventarisasi Bangunan dan Fasilitas Perlengkapan Jalan Pada Jalan Garuda Sakti - Mika Purba; Horas Saut MM; Sri Djuniati; Elianora; Dwi Visti Rurianti; Haji Gussyafri (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2025)
Jalan Garuda Sakti is a provincial road that connects Pekanbaru City and Kampar Regency and serves as the boundary between inner-city and outer-city road segments. Road buildings and traffic equipment facilities are essential components in supporting road functionality, safety, and user comfort. This study aims to inventory the availability and identify the needs of road buildings and equipment facilities along both segments. A quantitative approach was employed through field surveys. The results indicate that no road buildings were available on either inner-city or outer-city segments. Of the nine types of road equipment facilities assessed, the inner-city segment was equipped with only two types, namely traffic signs and street lighting, while the outer-city segment had only traffic signs. The analysis of facility requirements shows that the inner-city segment requires roadside drainage channels, 17 street lighting units, 32 traffic signs, and two types of road markings. Meanwhile, the outer-city segment requires roadside drainage channels, 33 street lighting units, 28 traffic signs, and two types of road markings. Overall, the findings reveal that road buildings and equipment facilities are still inadequate in both segments, particularly in the outer-city area, highlighting the need for accelerated infrastructure development to improve traffic safety, comfort, and  mobility.